Peter's chair - Keats, Ezra Jack. (New York : Harper & Row, 1967)
When Peter discovers his blue furniture is being painted pink for a new baby sister, he rescues the last unpainted item, a chair, and runs away.
Elem. School Library Collection.
School Library Journal.
Book Links (A.L.A.).
2.6
K-3
Center for the Collaborative Classroom Curriculum.
Keywords: African Americans -- Fiction; Brothers and sisters -- Fiction; Chairs -- Fiction; Babies -- Fiction